Effectiveness of plasmotherapy and ozone therapy in complex treatment of patients with generalized periodontitis - Борисенко, Анатолій Васильович; Случевська, Олена Олександрівна (Actual Dentistry, 2019)
Objective. Periodontal disease is the most widespread human disease. The problem of rational treatment of generalized periodontitis is relevant. In the complex treatment of generalized periodontitis, various groups of medicines are traditionally used. Nowadays, a great attention s being paid to the usage of plasmotherapy which is better to supply with ozone therapy. Aim of study. Analysis of the effectiveness of platelet-rich autoplasma and ozone therapy in the complex treatment of patients with generalized periodontitis. Materials and methods. Clinical study was performed in a group of 20 patients with generalized periodontitis. Patients received a comprehensive examination of the state of periodontal tissues before and after treatment. To evaluate a clinical efficacy of the treatment the PMA index (Parma C., 1961), OHI-S (1964) and CPITN index (1982) evaluation were used for control of treatment. Results. During the study, it was considered that addition of plasma therapy and ozone therapy in the complex treatment of patients with generalized periodontitis may provide more effectively decreasing the degenerative and inflammatory processes in periodontal tissues that was confirmed by decreasing of the levels of OHI-S, PMA and CPITN indexes. Conclusions. The usage of plasma therapy and ozone therapy in the complex treatment of patients with generalized periodontitis may increase the general effectiveness of treatment. Key words: generalized periodontitis, plasma therapy, ozone therapy.